Maine magic : a vivid portrayal of Maine life, Maine towns and islands, and Maine people ... - Caldwell, Bill; Murphy, Kimberly C. (Portland, Me. : G. Gannett Pub., 1979)
In this collection of stories, a newspaper columnist visits county fairs, off shore islands, and other unique and surprising places.
"Maine Magic is the sequel to Enjoying Maine"--Jacket flap.
Keywords: Caldwell, Bill -- Travel -- Maine; Maine -- Social life and customs; Maine -- Description and travel